Nutrition Products and Supplements from Amway (Nutrilite) / Nor Maisarah Mohd Harun - Mohd Harun, Nor Maisarah (2021)
Bismillahirahamanirahim. First and foremost, I would like to say thank you for being given this opportunity in doing such an interesting assignment. It is really great to get early experience on involving and handling in business by myself. I have learnt a lot on how to manage small business by helping my mother with her business too. I also would like to say thank you to my beloved lecturer named puan Hazelen Mat Rusok for always guiding me and teaching me the ways to do this ass correctly. Business opportunity is done by students to gain experiences by ourselves on how to manage a business. We are free to choose the types of business that we want to do based on our likes. We learn a lot while accomplishing this assignment. We learn to count the budget and profit that we get for the business, market the products, deal with costumers and other business problems.